Tirzepatide safety in type 2 diabetes: a disproportionality analysis of adverse events using the FDA FAERS database - Zhenpo Zhang; Jiangxiong Li; Jingping Zheng; Yankun Liang; Lin Ma; Ling Su (Endocrine Connections)
This study evaluated adverse events reported with tirzepatide, a dual GIP/GLP-1 receptor agonist approved for type 2 diabetes and obesity, using real-world data from the FDA Adverse Event Reporting System. A disproportionality analysis was conducted on reports from May 2022 to the fourth quarter of 2024. Reports were deduplicated, normalized using standardized medical terminology, and analyzed using four disproportionality analysis algorithms. Significant signals required meeting all four methods’ criteria with at least three cases. Among 20,350 adverse event reports (68.0% female; median age 50.4 years), 105 significant adverse events were identified. Common events included gastrointestinal disorders (nausea and diarrhea) and injection-site reactions. The strongest signals were injection-site coldness and belching. Known risks such as pancreatitis (190 cases) and hypoglycemia (115 cases) were confirmed. Novel signals included upper respiratory infections and postmenopausal hemorrhage. The median onset time was 26 days, with 50% of events occurring within the first month. Older adults (65 years or older) experienced earlier onset (12 versus 31 days, significant difference). This analysis is consistent with known gastrointestinal and pancreatic risks of tirzepatide from prior clinical studies and identifies potential new safety concerns, underscoring the need for vigilant monitoring, particularly during initial treatment phases.